2008
DOI: 10.1590/s1516-35982008000500011
|View full text |Cite
|
Sign up to set email alerts
|

Níveis de energia metabolizável em rações para frangos de corte mantidos em ambiente de alta temperatura

Abstract: RESUMO -Quatrocentas aves com peso médio de 675,00 g foram distribuídas em delineamento de blocos casualizados, com base no peso das aves, com cinco tratamentos e quatro repetições. As dietas experimentais foram constituídas de cinco níveis de energia metabolizável (2.800, 2.900, 3.000, 3.100 e 3.200 kcal de EM/kg de ração) formuladas para atender às exigências nutricionais, exceto de energia metabolizável. O aumento do nível de energia das rações foi obtido pela adição de óleo de soja. Realizaram-se análises … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
2
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 6 publications
0
4
2
7
Order By: Relevance
“…Meza et al [22] found CB carcass yield of 73.17%. The HB lineage according to Barbosa et al [23] presented 82.71% yield at 49 days of age.…”
Section: Yield -Cutsmentioning
confidence: 99%
“…Meza et al [22] found CB carcass yield of 73.17%. The HB lineage according to Barbosa et al [23] presented 82.71% yield at 49 days of age.…”
Section: Yield -Cutsmentioning
confidence: 99%
“…The stress caused by thermal environment influences endocrinology and physiology of the poultry, and, consequently, productivity, by changing their heat exchange with the environment and modify the rate of food consumption, the rate of body weight gain and the nutritional requirements (SOUZA et al, 2011;BARBOSA et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The nutritional plans did not affect liver and heart weights (P > 0.05); however, there was a significant effect on liver, gizzard, and small intestine weights. Ribeiro et al (2001), Rocha et al (2003), and Barbosa et al (2008) found no differences in the heart weight of birds under different nutritional plans. Table 10.…”
Section: Resultsmentioning
confidence: 88%